A matter of entrepreneurial decisions: Dairibord Holdings Limited (DHL) in Zimbabwe. Issue 3 (20th September 2018) - Simba, Amon
Abstract : Subject area: Entrepreneurship. Study level/applicability: Postgraduate and undergraduate. Case overview: The case study focussed on the dairy sector in the southern African country of Zimbabwe. It offered an analysis of the management and business development approaches DHL employed in the country's dairy sector. The narrative detailed how DHL's commercial performance progressively declined overtime. Several factors including operational inefficiencies, intensive competition, political, socio-economic issues and natural disasters were attributable to its decline. To mitigate DHL's business development challenges, Antony and his top management's reprised "restructure, expand and diversify" strategy only achieved inconsistent commercial results. The scale and size of these results unequivocally necessitated radical entrepreneurial methods to turnaround its fortunes. It was indeed a matter of entrepreneurial decisions! Methodology: The case study used secondary analysis as its main strategy for generating relevant data. The rationale for adopting the principles of secondary analysis was to take advantage of quality archived data, public and readily available information concerning DHL's commercial performance. Setting up to undertake secondary analysis for the purpose of DHL's narrative was less-expensive, and it was less time-consuming when compared to structured interviews and self-administered questionnaires. Hence, it was deemed appropriate for producing a narrative on a company whose archived financial reports and publicly available research information were accessible. Relevant course levels: DHL's narrative is relevant for students studying entrepreneurship, business management and international business at postgraduate and undergraduate levels. Theoretical basis: The multi-dimensional constructs of entrepreneurship and strategic management provided the theoretical basis for constructing a narrative about DHL's business activities in Zimbabwe's dairy sector. Particularly, the entrepreneurial decision-making paradigm offered some insight, direction and guidance in analysing the strategies Antony and his top management team applied in their planning and management at DHL. Equally, strategic management theories provided useful instructions for exploring business development issues in a rapidly changing business terrain that was presented by the dairy sector in Zimbabwe. Expected learning outcomes: By the end of the lesson students will have had the opportunity to identify the features of an organisation with an entrepreneurial mind set; evaluate the importance of making entrepreneurial decisions in a rapidly changing market such as the dairy industry in Zimbabwe; explore the sort of issues faced by large enterprises in establishing an entrepreneurial architecture; develop an appreciation of the importance of practicing entrepreneurial leadership in rapidly changing business conditions; analyse the importance of developing an effective strategy while considering strategic options necessary to withstand markets such as the dairy sector in Zimbabwe that are characterised with rapid changes. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject Code: CSS 3: Entrepreneurship.